Strategic Capability and Public Value in Online Gambling Enforcement: An Indonesian National Police Case Study - Arus Reka Prasetia; Puspo Dewi Dirgantari (Politeia : Journal of Public Administration and Political Science and International Relations, 2026)
Online gambling has become a major public governance and cyber law enforcement challenge in Indonesia due to its links to social harm, illicit financial flows, and threats to digital order. This article examines how the Indonesian National Police, particularly the Directorate of Cyber Crime within the Criminal Investigation Agency, mobilizes strategic capability in online gambling enforcement and how these enforcement patterns can be interpreted through a public value lens. The study employed a qualitative document-based single-case design using 21 screened public documents selected from 35 sources related to the 2022–2025 enforcement period. The corpus included performance reports, institutional statements, regulatory and policy documents, task-force coordination materials, and public analytical sources. Data were analyzed using thematic document analysis, pattern matching, and explanation building. The findings identify five strategic capabilities: integrated digital intelligence, accredited digital forensics, inter-agency coordination, public participation and reporting reach, and adaptive legal-investigative capability. These capabilities contribute to economic protection, social protection, and digital ecosystem integrity through intelligence-driven enforcement, financial disruption coordination, public reporting and preventive education, and digital ecosystem stewardship. Economic protection emerged as the strongest dimension, while digital ecosystem integrity remained the most interpretive because it relied on proxy indicators rather than standardized measurement. The article concludes that online gambling enforcement in Indonesia becomes strategically meaningful when police capability is directed not only toward case handling but also toward broader public value creation.